Neutron Reflectivity and Performance of Polyamide Nanofilms for Water Desalination. (2nd August 2017) - Foglia, Fabrizia; Karan, Santanu; Nania, Manuela; Jiang, Zhiwei; Porter, Alexandra E.; Barker, Robert; Livingston, Andrew G.; Cabral, João T.
Abstract : The structure and hydration of polyamide (PA) membranes are investigated with a combination of neutron and X‐ray reflectivity, and their performance is benchmarked in reverse osmosis water desalination. PA membranes are synthesized by the interfacial polymerization of m ‐phenylenediamine (MPD) and trimesoyl chloride (TMC), varying systematically reaction time, concentration, and stoichiometry, to yield large‐area exceptionally planar films of ≈10 nm thickness. Reflectivity is employed to precisely determine membrane thickness and roughness, as well as the (TMC/MPD) concentration profile, and response to hydration in the vapor phase. PA film thickness is found to increase linearly with reaction time, albeit with a nonzero intercept, and the composition cross‐sectional profile is found to be uniform, at the conditions investigated. Vapor hydration with H2 O and D2 O from 0 to 100% relative humidity results in considerable swelling (up to 20%), but also yields uniform cross‐sectional profiles. The resulting film thickness is found to be predominantly set by the MPD concentration, while TMC regulates water uptake. A favorable correlation is found between higher swelling and water uptake with permeance. The data provide quantitative insight into the film formation mechanisms and correlate reaction conditions, cross‐sectional nanostructure, and performance of the PA active layer in RO membranes for desalination. Abstract : The effect of reaction time, stoichiometry, and hydration on planar, nanofilm trimesoyl chloride (TMC)/m‐phenylenediamine (MPD) model reverse osmosis membranes is quantified by neutron and X‐ray reflectivity and correlated to membrane performance in water desalination. Film thickness increases linearly with reaction time, albeit with a nonzero intercept, and is predominantly set by the MPD concentration, while TMC regulates water uptake.